The Effect of Management Accounting Systems on Company Performance, External Environmental Uncertainty as a Moderating Variable - Muhammad Dahlan (BPJP - STEI, 2018)
The objective of this empirical research is how to effect of the relationship between management accounting systems and firm performance, and if the perceived environmental uncertainty as a moderating variable. The method of study is mail quesionaire destribute to units analysis of finance director or operation director or marketing director, and than we have 57,05% responcy rate. The results of this study indicate are the positively relationship between characteristics of management accounting information systems and firm performance, and do not confirm the effect of management accounting systems on the firm performance, if the perceived environmental uncertainty as a moderating variable. The second results were not consistent within previous research.